Coincidence point theorems for BKC-contraction mappings in generalized metric spaces endowed with a directed graph - Phakdi Charoensawan (2020)
© 2020 by TJM. All rights reserved. A new concept of generalized metric spaces and BKC-contractions are proposed while the existence of coincident points in these new settings is considered. In addition, an example as well as an application are provided to support our results.